Preparation method of high-specific-energy battery electrolyte and battery

By using cyclic sulfate compounds and unsaturated isocyanuride compounds as additives in high-specific energy battery electrolytes, combined with high content of FEC, a stable protective film is preferred to form a negative electrode and positive electrode, which solves the problem of difficulty in both storage performance and cycle life at high temperatures, and achieves long-term stability and high-efficiency performance of the battery.

CN119627210APending Publication Date: 2025-03-14ZHEJIANG RES INST OF CHEM IND CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311169268.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing high-specific energy battery electrolytes have difficulty in storage performance and cycle life at high temperatures, and FEC is prone to decomposition, resulting in deterioration of battery performance.

Method used

A cyclic sulfate compound and an unsaturated isocyanuride compound are used as additives, and a high content of fluorovinyl carbonate (FEC) is combined with the film-forming potential relationship of the additives, and a stable protective film is preferred to form a negative electrode and the positive electrode to inhibit the decomposition and side reaction of FEC.

Benefits of technology

It achieves the improvement of the battery's storage performance and the extension of the cycle life at high temperatures, reduces the initial impedance of the battery and the storage gas production, and ensures the long-term stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627210A_ABST
    Figure CN119627210A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-specific-energy battery electrolyte and application of the prepared electrolyte in a battery. The preparation method comprises the following steps: adding a main lithium salt into a non-aqueous solvent until the molar concentration of the main lithium salt is 0.8-1.6 mol / L, adding fluoroethylene carbonate which accounts for 0.5-50.0 wt% of the total mass of the electrolyte, and adding an additive; the additive comprises a cyclic sulfate compound serving as a first additive, and the cyclic sulfate compound accounts for 0.2-2.0 wt% of the total mass of the electrolyte; the unsaturated isocyanurate compound is used as a second additive and accounts for 0.1-1.0 wt% of the total mass of the electrolyte; specific structural definitions of the first additive and the second additive are shown in the specification. And the film-forming potentials Vca of the first additive, the second additive and the fluoroethylene carbonate at the negative electrode meet the following relation: Vca (first additive) < Vca (fluoroethylene carbonate) < Vca (second additive). The electrolyte can improve the high-temperature cycle life, the normal-temperature cycle life and the storage performance of the battery at the same time under a high-voltage system of the high-specific-energy battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-energy-density battery electrolyte, in particular to a preparation method of the high-energy-density battery electrolyte and application of the electrolyte prepared by the preparation method in high-energy-density batteries. Background Art

[0002] With the continuous development of technology, people have put forward requirements for higher energy density and longer cycle life for lithium-ion batteries. Using high-energy-density electrode materials or increasing the operating voltage of the battery are currently two effective ways. When fully charged, the positive and negative electrode materials of the battery are highly active and will undergo redox reactions with the electrolyte, rapidly deteriorating the battery performance. Especially in high-energy-density battery systems such as high-silicon negative electrodes and lithium metals, in order to achieve long cycle life, it is usually necessary to use a high content of fluoroethylene carbonate (abbreviated as "FEC") to continuously repair and stabilize the negative electrode interface film during the cycle process to improve the cycle performance. Although FEC can effectively improve the cycle life of high-energy-density batteries, it is easy to open the ring to decompose or defluorinate under the catalysis of high pressure, high temperature, high-valent metal ions and Lewis acidic compounds and produce a large amount of HF, further destroying the interface stability of the electrode material / electrolyte, aggravating the occurrence of side reactions, causing serious gas production in the battery, and deteriorating the high-temperature storage performance. In order to improve the gas generation problem of FEC during high-temperature storage, high-temperature gas generation inhibitory additives such as PS, MMDS, PST, and water removal and acid inhibition functional additives such as TPPI are generally used. However, these additives generally have high film formation impedance or deteriorate other electrochemical properties, and the storage performance improvement is not significant enough. Therefore, it is still difficult to achieve a balance between cycle life and storage performance.

[0003] Chinese patent CN105375066A discloses an electrolyte suitable for silicon-carbon negative electrode lithium-ion batteries, which uses a combination of sulfate, tris(trimethylsilyl)borate and FEC. The combination changes the components of the SEI film by controlling the amount of additives used, thereby reducing the battery impedance and improving the battery storage and cycle performance at the same time. However, the amount of FEC used in this method is low, which makes it difficult to meet the FEC consumption during long-term storage or cycling, and it is impossible to achieve long-term stable battery performance.

[0004] Chinese patent CN103730688A discloses a method for combining unsaturated oxalate with FEC, which combines 1,3-propane sultone (PS), divinyl oxalate and FEC, and uses the good film-forming characteristics of PS and unsaturated oxalate negative electrodes to reduce the decomposition and gas production of FEC and improve battery performance. In this method, PS is used in large quantities as the main additive to inhibit gas production, which will increase the internal resistance of the battery, thereby deteriorating the normal temperature cycle and high temperature cycle, and cannot guarantee long-cycle cycle performance.

[0005] Patent WO2018073694A1 discloses a cyanosiloxane for silicon negative electrode lithium batteries, which can reduce the HF content generated by FEC and inhibit gas production during high-temperature storage of the battery. However, the interfacial film formed by this compound at the silicon-based negative electrode interface is relatively unstable and is easily decomposed and gasified during long-term high-temperature cycles. This is not conducive to long-term high-temperature cycles and cannot fundamentally solve the problem of poor high-temperature stability of the electrolyte.

[0006] Therefore, improving the storage performance while increasing the high-temperature and room-temperature cycle life of high-energy-density batteries, and achieving a balance between high-temperature storage and cycle performance, are difficult problems that need to be solved in the current high-energy-density battery electrolyte system. Summary of the invention

[0007] In order to solve the problems existing in the background technology, the present invention proposes a method for preparing a high-energy-density battery electrolyte. The electrolyte prepared by the preparation method is applied to a high-energy-density battery system, which can take into account the battery's high-temperature cycle life, normal-temperature cycle life and battery storage performance.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a high-energy-density battery electrolyte, the method comprising: adding a main lithium salt to a non-aqueous solvent until the molar concentration of the main lithium salt is 0.8-1.6 mol / L, adding FEC accounting for 3.0-50.0 wt% of the total mass of the electrolyte, and adding additives; the additives include:

[0010] The first additive is selected from at least one of the cyclic sulfate compounds represented by the following structures (I-1), (I-2), (I-3) or (I-4), accounting for 0.2 to 2.0 wt% of the total mass of the electrolyte:

[0011]

[0012] In the formula, R1, R2, R3, R4, R5, R6, R7, R8 are independently selected from hydrogen, C1-C3 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C3 alkoxy, phenyl or phenoxy; m, n, z are independently selected from 0, 1 or 2; R9, R 10 are independently selected from hydrogen, C1-C3 alkyl or halogen, and hydrogen in R1, R2, R3, R4, R5, R6, R7, R8 is optionally substituted by halogen;

[0013] The second additive is selected from the unsaturated isocyanurate compound represented by the following formula (II), accounting for 0.1-1.0 wt% of the total mass of the electrolyte:

[0014]

[0015] In formula (II), R 11 , R 12 , R 13 is independently selected from C1-C6 alkyl, C1-C6 haloalkyl, C2-C6 alkenyl, C2-C6 haloalkenyl, C2-C6 alkynyl or C2-C6 haloalkynyl, and R 11 , R 12 , R 13 At least one of them is C2-C6 alkenyl, C2-C6 haloalkenyl, C2-C6 alkynyl or C2-C6 haloalkynyl;

[0016] Furthermore, the first additive, the second additive and the FEC have a film forming potential V at the negative electrode. ca The following relationship is met: V ca(第一添加剂) <V ca(FEC) <V ca(第二添加剂) .

[0017] Specifically, the first additive has a film-forming potential at the negative electrode.

[0018] In this way, the first additive can preferentially reduce FEC at the negative electrode to form a stable SEI film, thereby reducing the decomposition of FEC in the formation stage and the occurrence of FEC side reactions at the negative electrode during circulation and storage, inhibiting battery gas production, improving battery storage performance, and maximizing the role of FEC in improving cycle life.

[0019] At the same time, the first additive, the second additive and the FEC have a film forming potential V at the positive electrode. an The following relationship is met: V an(第二添加剂) <V an(第一添加剂) <V an(FEC) .

[0020] In this way, the second additive can preferentially oxidize and decompose FEC at the positive electrode, forming a stable protective film, inhibiting the parasitic reaction between the electrolyte and the positive electrode material, inhibiting the dissolution of positive electrode metal ions such as Ni and Co, thereby improving the stability of the positive electrode material and improving the cycle life; and the positive electrode protective film formed by the second additive can reduce the contact reaction between FEC and the positive electrode, inhibiting the generation of gas during storage and circulation. At the same time, the present invention has also found through research that the second additive also has the effect of removing water and inhibiting acid, can remove trace water in the electrolyte, inhibit the generation of HF and PF5, and then inhibit the decomposition of FEC, reducing the gas generation during battery storage.

[0021] In addition, the first additive forms a film on the negative electrode before the second additive, which can inhibit the second additive from forming a film on the negative electrode, thereby reducing the battery impedance. Therefore, through the synergistic effect of the first additive, the second additive and FEC, the decomposition of FEC in the initial stage and long-term storage or cycling can be reduced, and the generation of gas during storage can be inhibited. At the same time, the battery impedance can be reduced and the battery cycle life can be improved, thereby achieving high specific energy batteries with long cycle life (high temperature cycle and normal temperature cycle) and maintaining excellent storage performance.

[0022] Preferably, in the preparation process of the high specific energy battery electrolyte, 0.5 to 45.0 wt% of FEC is added to the total mass of the electrolyte, and more preferably 1.0 to 40.0 wt% of FEC is added to the total mass of the electrolyte.

[0023] Furthermore, the first additive is selected from at least one of the cyclic sulfate compounds shown in the following structures:

[0024]

[0025] In the second additive, R 11 , R 12 , R 13 are independently selected from C1-C3 alkyl, C1-C3 haloalkyl, C2-C4 alkenyl or C2-C4 alkynyl, and R 11 , R 12 , R 13 At least one of them is a C2-C4 alkenyl group or a C2-C4 alkynyl group.

[0026] Further preferably, the second additive is selected from at least one of the unsaturated isocyanurate compounds shown in the following structures:

[0027]

[0028] In order to improve the comprehensive performance of high specific energy batteries, the basic additive is selected from at least one of vinyl carbonate, tris(trimethylsilyl) phosphate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorophosphate bis(oxalate), lithium difluorophosphoryloxyfluoroborate, pyrosulfate boron trifluoride composite lithium salt or lithium difluorooxalate borate, and the amount of any one of the basic additives accounts for 0.1 to 2.0 wt% of the total mass of the electrolyte, and any one of the basic additives is different from the main lithium salt.

[0029] According to the above-mentioned method for preparing the high specific energy battery electrolyte, the main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide or lithium bis(trifluoromethylsulfonyl)imide.

[0030] According to the preparation method of the aforementioned high-energy-density battery electrolyte, the non-aqueous solvent includes a linear solvent and a cyclic solvent, the linear solvent is selected from at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, methyl propyl carbonate or propyl propionate; the cyclic solvent is selected from at least one of ethylene carbonate, propylene carbonate, FEC, γ-butyrolactone or γ-valerolactone.

[0031] The present invention also provides a high specific energy battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the high specific energy battery is prepared by the following method:

[0032] The positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any of the above-mentioned preparation methods is injected into it, and a high-energy-density battery is obtained after standing, forming, volume separation and aging.

[0033] In particular, the consumption of the first additive of the present invention in the formation process accounts for more than 70%, preferably more than 80% of the total amount of the first additive added. That is, the first additive of the present invention is mostly consumed in the initial formation process, which can reduce the consumption of FEC in the initial formation process.

[0034] Therefore, the amount of the first additive added during the preparation process of the present invention and the content in the electrolyte liquid of the prepared high-energy-density battery vary greatly. Specifically, in the high-energy-density battery, the first additive accounts for 0.06-0.6wt% of the total mass of the electrolyte liquid, the second additive accounts for 0.1-1.0wt% of the total mass of the electrolyte liquid, and FEC accounts for 0.4-36.0wt% of the total mass of the electrolyte liquid. Preferably, FEC accounts for 0.8-32.0wt% of the total mass of the electrolyte liquid.

[0035] The active material of the positive electrode plate of the present invention is lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials, nickel-cobalt-manganese ternary materials Li (Ni x Co y Mn z )O2, x>0.5, y≥0, z>0, x+y+z=1, or nickel-cobalt-aluminum ternary material Li(Ni x Co y Al z )O2, x>0.8, y>0, z>0, x+y+z=1; the active material of the negative electrode plate is lithium metal, silicon-carbon composite material or graphite material.

[0036] The energy density of the high specific energy battery is >250Wh / kg.

[0037] The high specific energy battery has a charge cut-off voltage higher than 4.2V, and a discharge cut-off voltage lower than 2.8V.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The present invention adopts a first additive, a second additive and FEC in combination. The first additive can form a stable SEI film at the negative electrode in priority to FEC and the second additive. The second additive can quickly react with trace water in the system to inhibit the generation of HF and PF5. At the same time, the second additive forms a stable protective film at the positive electrode before the first additive, which can avoid the ineffective decomposition of the first additive and FEC in the initial formation process and produce gas. Through the synergistic effect of the three, the optimal configuration of the usage and function of the additives is achieved, thereby effectively reducing the initial impedance of the battery, improving the long-term storage performance and cycle performance of the battery, and achieving a balance between high-temperature storage performance and cycle life.

[0040] 2. The first additive of the present invention can inhibit the oxidation product of the second additive from shuttling to the negative electrode to form a film, reduce the decomposition of the second additive, and thus reduce the usage of the second additive.

[0041] 3. The second additive of the present invention can react with trace water in the electrolyte, inhibit the generation of PF5 and HF in the electrolyte system, improve the stability of the electrolyte system, and further inhibit the decomposition of FEC under the catalysis of Lewis acidity, thereby slowing down the consumption of FEC. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 LSV reduction curves of Base electrolyte 2, Tset electrolyte 1, Tset electrolyte 2 and Tset electrolyte 3 of the present invention;

[0043] Figure 2 These are the LSV oxidation curves of the Base electrolyte 2 and the Tset electrolyte 1, Tset electrolyte 2 and Tset electrolyte 3 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0045] 1. Preparation of electrolyte

[0046] Preparation of Base electrolyte 1: In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are evenly mixed in a mass ratio of EC:DEC:EMC=3:2:5, and lithium hexafluorophosphate (LiPF6) is slowly added to the mixed solution until the molar concentration of LiPF6 is 1.0 mol / L to obtain Base electrolyte 1.

[0047] Example 1

[0048] 1.0% of compound A13, 0.5% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0049] Example 2

[0050] 1.0% of compound A13, 1% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0051] Example 3

[0052] 2.0% of compound A13, 0.5% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0053] Example 4

[0054] 1.0% of compound A13, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0055] Example 5

[0056] 1.0% of compound A1, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0057] Example 6

[0058] 1.0% of compound A11, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte solution 1 to obtain the electrolyte solution of this example.

[0059] Example 7

[0060] 1.0% of compound A13, 0.2% of compound B6 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0061] Example 8

[0062] 1.0% of compound A13, 0.2% of compound B9 and 10% of FEC were added to the base electrolyte solution 1 to obtain the electrolyte solution of this example.

[0063] Example 9

[0064] 1.0% of compound A13, 0.2% of compound B3 and 5% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0065] Example 10

[0066] 1.0% of compound A13, 0.2% of compound B3 and 20% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0067] Embodiment 11

[0068] 1.0% of compound A13, 0.2% of compound B3 and 40% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0069] Example 12

[0070] 0.5% of compound A13, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0071] Example 13

[0072] 1.0% of compound A13, 0.2% of compound B3, 10% of FEC and 0.8% of compound LiDFP were added to the base electrolyte solution 1 to obtain the electrolyte solution of this example.

[0073] Embodiment 14

[0074] 1.0% of compound A13, 0.2% of compound B3, 10% of FEC and 2% of compound LiFSI were added to the Base electrolyte 1 to obtain the electrolyte of this example.

[0075] Embodiment 15

[0076] 1% of compound A2, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0077] Example 16

[0078] 1% of compound A6, 0.2% of compound B2 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0079] Embodiment 17

[0080] 1% of compound A11, 0.2% of compound B1 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0081] Embodiment 18

[0082] 1% of compound A11, 0.2% of compound B12 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0083] Embodiment 19

[0084] 1% of compound A11, 0.2% of compound B3 and 1% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this example.

[0085] Embodiment 20

[0086] In the Base electrolyte 1, 1% of compound A11, 0.2% of compound B3, 10% of FEC and 1% of the compound lithium difluorophosphoryloxyborofluoride (LiB2PF8O2) were added to obtain the electrolyte of this embodiment.

[0087] Comparative Example 1

[0088] Base electrolyte 1 was used as the electrolyte of this comparative example.

[0089] Comparative Example 2

[0090] Only 0.2% of the compound TMSP was added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0091] Comparative Example 3

[0092] 1.0% of compound VC was added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0093] Comparative Example 4

[0094] 10% of FEC was added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0095] Comparative Example 5

[0096] Only 1.0% of Compound A13 was added to Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0097] Comparative Example 6

[0098] Only 0.2% of compound B3 was added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0099] Comparative Example 7

[0100] 1.0% of Compound A13 and 10% of FEC were added to Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0101] Comparative Example 8

[0102] 0.2% of compound B3 and 10% of FEC were added to Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0103] Comparative Example 9

[0104] 1.0% of compound A13 and 0.2% of compound B3 were added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0105] Comparative Example 10

[0106] 1.0% of Compound A13, 0.2% of TMSP and 10% of FEC were added to Base electrolyte 1 to obtain an electrolyte of this comparative example.

[0107] Comparative Example 11

[0108] 1.0% VC, 0.2% TMSP and 10% FEC were added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0109] Comparative Example 12

[0110] 3.0% of compound A13, 0.2% of compound B3 and 10% of FEC were added to the base electrolyte 1 to obtain the electrolyte of this comparative example.

[0111] Comparative Example 13

[0112] 1.0% of compound A13, 0.2% of compound B3 and 60% of FEC were added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0113] Comparative Example 14

[0114] 1.0% of compound A13, 2% of compound B3 and 10% of FEC were added to the Base electrolyte 1 to obtain the electrolyte of this comparative example.

[0115] 2. Electrochemical performance test

[0116] (I) Redox performance test (LSV)

[0117] In order to avoid the interaction between the solvent and the additive in the complex electrolyte formula of the embodiment / comparative example and thus affect the redox potential, the Tset electrolyte for LSV test is prepared, comprising the following steps:

[0118] In a glove box filled with argon (water content <5ppm, oxygen content <10ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were uniformly mixed at a mass ratio of EC:EMC=3:7, and lithium hexafluorophosphate (LiPF6) was slowly added to the mixed solution until the molar concentration of LiPF6 was 1.0 mol / L to obtain Base electrolyte 2, and then 2% of the test compound was added to Base electrolyte 2, as shown in Table 1 below:

[0119] Table 1 Electrolyte formula used in LSV test

[0120]

[0121] LSV oxidation potential test: Pt was used as the working electrode, the counter electrode and the working electrode were lithium metal respectively, the electrolytes were Base electrolyte 2 and Test electrolyte respectively, the test voltage range was OCV~6.5V, the scanning speed was 0.2mV / s, the oxidation curves of Base and Test electrolytes were recorded, and the oxidation decomposition potential of the test compound was determined.

[0122] LSV reduction potential test: graphite was used as the working electrode, the counter electrode and the working electrode were lithium metal respectively, the electrolytes were Base electrolyte 2 and Test electrolyte respectively, the test voltage range was OCV~0.01V, the scanning speed was 0.1mV / s, the reduction curves of Base and Test electrolytes were recorded, and the reduction decomposition potential of the test compound was determined.

[0123] Attached Figure 1 and attached Figure 2 The LSV reduction curves and LSV oxidation curves of the Base electrolyte 2 (mainly the solvent EC) and the compound A11, compound B3 and FEC in the Base electrolyte 2 of the present invention are given respectively. Figure 1 , Figure 2It can be seen that the reduction decomposition potential of FEC is about 0.88V, and there is no obvious oxidation decomposition potential; the reduction decomposition potential of EC is about 0.64V, and there is also no obvious oxidation decomposition potential; the reduction decomposition potential of compound A11 is about 1.06V, and there is also no obvious oxidation decomposition potential; compound B3 has no obvious reduction decomposition potential, but its oxidation decomposition potential is about 4.91V. By comparing the reduction potential, it can be seen that the order of film formation of the above compounds at the negative electrode is compound A11>FEC>EC, and the order of film formation at the positive electrode is compound B3>EC, and other compounds have no positive electrode film formation effect. Although compound A11 has no obvious positive electrode film formation effect in the LSV curve, its reduction product can shuttle to the positive electrode to participate in the positive electrode film formation in the full battery; similarly, compound B3 only has an oxidation decomposition potential, and its decomposition product can also shuttle to the negative electrode to participate in the negative electrode film formation; but this oxidation and reduction decomposition product shuttles between the positive and negative electrodes and then forms a film, which may deteriorate the battery performance.

[0124] pass Figure 1 , Figure 2 The LSV curve also shows that the first additive is a negative electrode film-forming additive and its film-forming potential is higher than that of FEC, while the second additive is a positive electrode film-forming additive. Therefore, in the formation stage, the first additive can be preferentially decomposed to form a good interface film, thereby reducing the consumption of FEC.

[0125] (II) Performance test

[0126] The electrolytes of the above-mentioned embodiments and comparative examples are respectively made into soft-pack lithium-ion batteries with a capacity of 1500 mAh. The lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is a ternary positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2, the negative electrode active material is a silicon-carbon composite material. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished soft-pack battery cell is obtained through the processes of standing, forming, volume separation and aging.

[0127] The prepared lithium-ion power battery (soft-pack battery cell) was subjected to performance testing. The specific test items and methods are as follows:

[0128] 1. Changes in additive content before and after formation are shown in Table 2 below:

[0129] Table 2 Content of additives in the electrolyte before and after battery formation

[0130]

[0131]

[0132]

[0133] According to Table 2 above, whether the first additive is used alone or in combination with other additives, its consumption rate in the formation stage is above 80%; when the second additive is used alone, its consumption rate in the formation stage is 50%, but when the second additive is used in combination with the first additive, FEC and other additives with negative electrode film-forming effect, the consumption in the formation stage is ≤10%, which is basically no consumption; when FEC is used alone, the consumption in the formation stage is about 40%, but when used in combination with the first additive, the consumption is about 10-15%, and when used in combination with VC and TMSP, the consumption is 34%. Compared with the combination of FEC and the first additive, the combined composition of FEC, the first additive and the second additive, or the combined composition of FEC, the first additive and TMSP, has no significant change in the consumption of FEC in the formation stage. When the first additive, the second additive and FEC are used in combination, the consumption of the second additive in the formation stage is ≤10%, the consumption of FEC in the formation stage is ≤15%, and the consumption of FEC in the formation stage is >30% when VC, TMSP and FEC are used in combination. The present application realizes the effective allocation of the consumption of additives after formation through the synergistic effect of additives.

[0134] 2. Electrochemical performance test:

[0135] (1) 60℃ high temperature storage test: Before storage, cycle 1 cycle at 0.5C / 0.5C at room temperature, record the discharge capacity, internal resistance and volume of the first cycle, then charge to 4.20V at 0.5C constant current, and charge at constant voltage until the current drops to 0.05C, stand in a 60℃ constant temperature oven for 60 days, then cycle 2 cycles at 0.5C / 0.5C at room temperature, record the discharge capacity of the first cycle after high temperature standing, the discharge capacity of the second cycle, the internal resistance and volume after storage. Calculate the capacity retention rate, capacity recovery rate, internal resistance growth rate and volume expansion rate of the battery after storage according to the following formula:

[0136] Capacity retention rate = discharge capacity of the first cycle after high-temperature standing (after storage) / discharge capacity of the first cycle (before storage) * 100%.

[0137] Capacity recovery rate = discharge capacity of the second cycle after high-temperature standing (after storage) / discharge capacity of the first cycle (before storage) * 100%.

[0138] Volume expansion rate = (volume after storage - volume before storage) / volume in the first week * 100%.

[0139] (2) 25°C high temperature cycle test: The battery is cycled at a charge and discharge current of 1C / 1C in a room temperature environment of 25±1°C, and the discharge capacity per week is calculated. The cycle is stopped when the capacity retention rate is less than 80%.

[0140] (3) 45℃ high temperature cycle test: The battery is cycled in a 45±1℃ oven at a charge and discharge current of 1C / 1C, and the discharge capacity per week is calculated. The cycle is stopped when the capacity retention rate is less than 80%. The battery electrochemical performance test results are shown in Table 3 below:

[0141] Table 3 Battery electrochemical performance test results

[0142]

[0143]

[0144] By comparing Examples 4 to 6, Comparative Example 5 and Comparative Example 7 in Table 3 above, it can be found that the first additive cyclic sulfate compound can reduce the initial impedance of the battery, reduce storage gas production, and improve room temperature cycle performance; by comparing Examples 6 to 8 and Comparative Examples 6 to 9, it can be seen that although the second additive will increase the initial impedance, it can reduce the high-temperature storage gas production; by comparing Examples 9 to 11, Comparative Examples 4 and 7 to 9, it can be seen that FEC can improve room temperature and high temperature cycle performance, but will increase storage gas production; by comparing Example 4 and Comparative Examples 7 to 9, it can be seen that the combination of the first additive, the second additive and FEC can significantly reduce the initial impedance of the battery, reduce gas generation during long-term storage, increase storage capacity, and improve room temperature and high temperature cycle performance compared to the combination of any two additives.

[0145] By comparing Example 4 with Comparative Examples 10 and 11, it can be seen that although VC has a negative electrode film-forming effect, TMSP has a positive electrode film-forming effect, and has a water removal and acid suppression function, the two compounds replace the first additive and the second additive respectively and are used in combination with FEC, and the improvement of battery performance is not as good as the combination of the first additive, the second additive and FEC. Combined with the data in Table 2, the main reason is that the combination of the first additive, the second additive and FEC can reduce the consumption of FEC in the formation stage, so that more FEC participates in interface repair in the later long cycle process, and at the same time can inhibit the consumption of the second additive in the formation stage, reduce the initial impedance of the battery, thereby achieving low impedance, gas production inhibition and long cycle performance.

[0146] In summary, the present invention provides a combination of cyclic sulfate compounds, unsaturated isocyanate compounds and FEC. The cyclic sulfate compounds can reduce the consumption of FEC in the formation stage and inhibit the negative electrode film formation of unsaturated isocyanate compounds. The unsaturated isocyanate compounds as positive electrode film-forming additives can not only inhibit storage gas production but also have the effect of removing water and inhibiting acid, thereby reducing the side reactions of FEC and electrolyte components. The three compounds work together to achieve low impedance, low gas production for long-term storage and improve the cycle life at room temperature and high temperature in a high energy density battery system, thereby achieving a balance between energy density and electrochemical performance.

Claims

1. A method for preparing a high specific energy battery electrolyte, characterized in that: The preparation method comprises: adding a main lithium salt to a non-aqueous solvent until the molar concentration of the main lithium salt is 0.8 to 1.6 mol / L, adding 0.5 to 50.0 wt% of fluoroethylene carbonate accounting for the total mass of the electrolyte, and adding additives; the additives comprise: The first additive is selected from at least one of the cyclic sulfate compounds represented by the following structures (I-1), (I-2), (I-3) or (I-4), accounting for 0.2 to 2.0 wt% of the total mass of the electrolyte: In the formula, R1, R2, R3, R4, R5, R6, R7, R8 are independently selected from hydrogen, C1-C3 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C3 alkoxy, phenyl or phenoxy; m, n, z are independently selected from 0, 1 or 2; R9, R 10 are independently selected from hydrogen, C1-C3 alkyl or halogen, and hydrogen in R1, R2, R3, R4, R5, R6, R7, R8 is optionally substituted by halogen; The second additive is selected from the unsaturated isocyanurate compound represented by the following formula (II-1) or (II-2), accounting for 0.1 to 1.0 wt% of the total mass of the electrolyte: In the formula, R 11 , R 12 , R 13 is independently selected from C1-C6 alkyl, C1-C6 haloalkyl, C2-C6 alkenyl, C2-C6 haloalkenyl, C2-C6 alkynyl or C2-C6 haloalkynyl, and R 11 , R 12 , R 13 At least one of them is C2-C6 alkenyl, C2-C6 haloalkenyl, C2-C6 alkynyl or C2-C6 haloalkynyl; Furthermore, the film forming potential V of the first additive, the second additive and the fluoroethylene carbonate at the negative electrode is ca The following relationship is met: V ca(第一添加剂) <V ca(氟代碳酸乙烯酯) <V ca(第二添加剂) .

2. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: Add 0.5-45.0wt% of fluoroethylene carbonate to the total mass of the electrolyte.

3. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: The first additive is in the negative electrode 4. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: The first additive is selected from at least one of the cyclic sulfate compounds shown in the following structures:

5. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: In the second additive, R 11 , R 12 , R 13 are independently selected from C1-C3 alkyl, C1-C3 haloalkyl, C2-C4 alkenyl or C2-C4 alkynyl, and R 11 , R 12 , R 13 At least one of them is a C2-C4 alkenyl group or a C2-C4 alkynyl group.

6. The method for preparing the high specific energy battery electrolyte according to claim 5, characterized in that: The second additive is selected from at least one of the unsaturated isocyanurate compounds shown in the following structures:

7. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: The additives also include basic additives, which are selected from at least one of vinyl carbonate, tris(trimethylsilyl) phosphate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorophosphate bis(oxalate), lithium difluorophosphoryloxyfluoroborate, pyrosulfate boron trifluoride composite lithium salt or lithium difluorooxalate borate, and the amount of any one of the basic additives accounts for 0.1 to 2.0 wt% of the total mass of the electrolyte.

8. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

9. The method for preparing the high specific energy battery electrolyte according to claim 1, characterized in that: The non-aqueous solvent includes a linear solvent and a cyclic solvent, wherein the linear solvent is selected from at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, methyl propyl carbonate or propyl propionate; and the cyclic solvent is selected from at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, γ-butyrolactone or γ-valerolactone.

10. A high specific energy battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The high specific energy battery is prepared by the following method: The positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any preparation method described in claims 1-9 is injected therein, and a high specific energy battery is obtained after standing, forming, volume separation and aging.

11. The high specific energy battery according to claim 10, characterized in that: The consumption of the first additive in the formation process accounts for more than 70% of the total added amount of the first additive.

12. The high specific energy battery according to claim 11, characterized in that: In the high specific energy battery, the first additive accounts for 0.06-0.6wt% of the total mass of the electrolyte liquid, the second additive accounts for 0.1-1.0wt% of the total mass of the electrolyte liquid, and fluoroethylene carbonate accounts for 0.4-36.0wt% of the total mass of the electrolyte liquid.

13. The high specific energy battery according to claim 10, characterized in that: The active material of the positive electrode plate is lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials, nickel-cobalt-manganese ternary materials Li (Ni x Co y Mn z )O2, x>0.5, y≥0, z>0, x+y+z=1, or nickel-cobalt-aluminum ternary material Li(Ni x Co y Al z )O2, x>0.8, y>0, z>0, x+y+z=1; the active material of the negative electrode plate is lithium metal, silicon-carbon composite material or graphite material.

14. The high specific energy battery according to any one of claims 10 to 13, characterized in that: The energy density of the high specific energy battery is >250Wh / kg.

15. The high specific energy battery according to claim 14, characterized in that: The high specific energy battery has a charge cut-off voltage higher than 4.2V, and a discharge cut-off voltage lower than 2.8V.

Citation Information

Patent Citations

  • Lithium ion battery and electrolyte thereof

    CN103730688A

  • Electrolyte suitable for silicon-carbon negative electrode lithium ion battery and silicon-carbon negative electrode lithium ion battery

    CN105375066A

  • Electrolyte solutions and electrochemical cells containing same

    WO2018073694A2